Analysis of Risk Factors and Nursing Strategies for Unplanned Extubation in Children: Retrospective Cohort Study - Xuefeng Han; Hairong Liu; Tingchong Zhang; Guangxin Fan (JMIR Nursing)
Abstract BackgroundUnplanned extubation (UEX) is a critical indicator of nursing care quality. Existing research primarily focuses on pediatric intensive care units (PICUs), with limited data available from general pediatric surgery. Currently, most studies on this topic are mainly focused on PICUs, and there is a lack of research data regarding general pediatric surgery. Therefore, further research should be conducted based on this consideration. ObjectiveThis study aimed to analyze the high-risk factors for UEX in children and implement appropriate nursing strategies to reduce its incidence, ensuring clinical safety of pediatric patients. MethodsA retrospective study (January 2018 - December 2023) included pediatric patients with indwelling catheters in general surgery. Exclusion criteria included mental disorders or abnormal Glasgow Coma Scale scores. Data on catheter days, UEX incidents, and risk factors were analyzed. ResultsA total of 1977 catheter days were recorded during the perioperative period, comprising 1079 days with urinary catheters, 768 days with postoperative wound drainage tubes, 68 days with gastric tubes, 46 days with peripheral central venous catheters, and 8 days with central venous catheters. During this period, 13 incidents of UEX occurred, yielding an overall UEX rate of 6.58 per 1000 catheter days. Urinary catheters accounted for the highest proportion of UEX incidents (8/13, 61.5%), followed by gastric tubes (3/13, 21.3%) and postoperative wound drainage tubes (2/13, 15.4%). The reintubation rate following UEX was 15.38% (2/13). Further analysis identified significant risk factors associated with UEX: (1) patient characteristics: age ≤3 years (8/13, 61.5%) and male sex (10/13, 76.9%); (2) clinical management: absence of physical restraints (10/13, 76.9%); and (3) temporal factors: incidents occurring during holidays (9/13, 69.2%). Multivariate analysis revealed that UEX risk was influenced by inter-related factors, including pediatric physiological characteristics (eg, limited self-regulation capacity), suboptimal catheter fixation methods, positional discomfort during patient movement, and variations in nursing interventions (eg, frequency of rounds and caregiver education). ConclusionsUnplanned extubation in pediatric inpatients represents a critical clinical complication that may compromise treatment efficacy and prolong hospitalization. Our findings highlight the multifactorial etiology of UEX events, with risk determinants spanning patient characteristics, care protocols, and environmental factors. To mitigate these risks, we propose implementing evidence-based multidisciplinary preventive strategies, including standardized risk assessment protocols for high-risk subgroups (eg, male patients aged ≤3 years), enhanced staff training on age-appropriate restraint techniques and securement device utilization, and dynamic adjustment of nursing surveillance frequency during peak risk periods (eg, holidays or postural changes). This systematic approach demonstrates potential to reduce UEX-associated adverse events by 42%‐68%, according to benchmark studies, ultimately improving pediatric care quality.